RONIN/HCF1‐TFEB Axis Protects Against D‐Galactose‐Induced Cochlear Hair Cell Senescence Through Autophagy Activation - Yongjie Wei; Yuhua Zhang; Wei Cao; Nan Cheng; Yun Xiao; Yongjun Zhu; Yan Xu; Lei Zhang; Lingna Guo; Jun Song; Su‐hua Sha; Buwei Shao; et al. (Advanced Science)
Abstract Age‐related hearing loss is characterized by senescent inner ear hair cells (HCs) and reduced autophagy. Despite the improved understanding of these processes, detailed molecular mechanisms underlying cochlear HC senescence remain unclear. Transcription Factor EB (TFEB), a key regulator of genes associated with autophagy and lysosomes, crucially affects aging‐related illnesses. However, intricate regulatory networks that influence TFEB activity remain to be thoroughly elucidated. The findings revealed that RONIN (THAP11), through its interaction with host cell factor C1 (HCF1/HCFC1), modulated the transcriptional activity of Tfeb, thus contributing to the mitigation (D‐galatactose [D‐gal]) senescent HC loss. Specifically, RONIN overexpression improved autophagy levels and lysosomal activity and attenuated changes associated with the senescence of HCs triggered by D‐gal. These findings highlight the possibility of using RONIN as a viable therapeutic target to ameliorate presbycusis by enhancing the TFEB function.